Corridors at Crossroads: Linear Development-Induced Ecological Triage As a Conservation Opportunity - Habib, Bilal; Rajvanshi, Asha; Mathur, Vinod B.; Saxena, Akanksha (Frontiers in Ecology and Evolution, 2016)
The transportation infrastructure of a nation forms the backbone of its economic growth and social development, and, as a developing country, India is no exception. However, with imperatives to improve connectivity for economic and social growth, ecological costs are often at stake. Roads, old and new, cut through protected forests and connecting habitats, resulting in a plethora of ecological effects. These may include the severing of natural corridors thereby compromising the role of landscapes as conservation units especially for landscape-dependent wild animal species. Consequent loss of biodiversity and ecosystems and decline in innumerable ecosystem services emanating from these natural reserves are other serious impacts. As India aspires for better, modern roads, the ecological concerns regarding many road upgradation projects have recently been the cause of disputes between the transportation sector and the conservation community. Delayed consideration of ecological concerns into linear development project planning leads to inadequate appropriation of funds needed for mitigating impacts of such developments. It is in these circumstances that the question of prioritizing areas and strategies for mitigation given limited mitigation funds arises. We examine the different facets to the debate of triage vis-à-vis conservation, development and mitigation planning in the transportation sector in a developing country context. We suggest that it is important and possible to secure investment towards conservation in areas outside the purview of legal protection through project mitigation costs and other mechanisms. We also make suggestions to avoid the ‘laissez-faire’ approach to linear development projects that is prevalent in India.